Implications of the evacuation of hospitalized patients in a nuclear emergency - Yasuda, Hiroshi (Frontiers in Public Health, 2023)
In the accident at the Fukushima Daiichi nuclear power station following the Great East Japan Earthquake and tsunami, more than 50 hospital patients died during or soon after evacuation, primarily owing to the interruption of necessary medical care. To prevent the occurrence of such losses in the future, the focus of evacuation decisions should be on the health status of individual patients and not on currently evaluated non-human aspects such as the geophysical conditions and the status of the accident facility. This brief research report provides a conceptual basis considering the principle of justification for making more appropriate decisions on the evacuation of hospitalized patients by balancing radiological risks and evacuation-induced health risks. This research report is expected to foster discussions among stakeholders on how to protect vulnerable people more appropriately in nuclear emergencies.